The Direct Measurement of Welfare Levels: How Much Does it Cost to Make Ends Meet? - Danziger, Sheldon; van der Gaag, Jacques; Taussig, Michael K.; Smolensky, Eugene (The Review of Economics and Statistics, 1984)
Sheldon Danziger, Jacques van der Gaag, Michael K. Taussig, Eugene Smolensky, The Direct Measurement of Welfare Levels: How Much Does it Cost to Make Ends Meet?, The Review of Economics and Statistics, Vol. 66, No. 3 (Aug., 1984), pp. 500-505